High barley intake in non-obese individuals is associated with high natto consumption and abundance of butyrate-producing bacteria in the gut: a cross-sectional study - Maruyama, Satoko; Matsuoka, Tsubasa; Hosomi, Koji; Park, Jonguk; Murakami, Haruka; Miyachi, Motohiko; Kawashima, Hitoshi; Mizuguchi, Kenji; Kobayashi, Toshiki; Ooka, Tadao; Yamagata, Zentaro; Kunisawa, Jun (Frontiers in Nutrition, 2024)
Objective: Barley, abundant in β-glucan, a soluble dietary fiber, holds promise in obesity prevention. Given the microbial metabolism of dietary fiber in the gastrointestinal tract, we investigated the role of gut microbiota in non-obese individuals consuming high levels of barley. Methods: Our study enrolled 185 participants from "The cohort study on barley and the intestinal environment (UMIN000033479)." Comprehensive physical examinations, including blood tests, were conducted, along with separate assessments of gut microbiome profiling and dietary intake. Participants were categorized into high and low barley consumption groups based on the median intake, with nonobese individuals in the high intake group identified as barley responders while participants with obesity were designated as non-responders. We compared the relative abundance of intestinal bacteria between these groups and used multivariate analysis to assess the association between intestinal bacteria and barley responders while controlling for confounding factors. Results and Discussion: Among the fermented food choices, responders exhibited notably higher consumption of natto (fermented soybeans) than non-responders. Moreover, after adjusting for confounders, Butyricicoccus and Subdoligranulum were found to be significantly more prevalent in the intestines of responders. Given natto's inclusion of Bacillus subtilis, a glycolytic bacterium, and the butyrateproducing capabilities of Butyricicoccus and Subdoligranulum, it is hypothesized that fiber degradation and butyrate production are likely to be enhanced within the digestive tract of barley responders.